CHRONIC ITCHING DERMATOSIS IN CHILDREN: MODERN METHODS OF TREATMENT AND EFFICIENT TERMINATION OF SUBJECTIVE COMPLAINTS - N. N. Murashkin; E. T. Ambarchyan; A. I. Materikin; R. V. Epishev (Union of pediatricians of Russia, 2016)
The article presents contemporary data on the peculiarities of etiology and pathogenesis of chronic itching dermatosis in children. We provide classification of various itching forms and pathophysiological mechanism of the development thereof underlying chronic skin disorders. We describe results of clinical studies of effectiveness and safety of methylprednisolone aceponate for treating itching dermatosis in children.